DAMPAK PENGGUNAAN METODE NILAI WAJAR TERHADAP NILAI PERUSAHAAN - Dika Nurita; Josin Sitinjak; Endang Kartini Panggiarti (Universitas Dian Nuswantoro, 2023)
The use of fair value metode is something that affects the value of the company.Â This study aims to test the impact of using the fair value method on company value. This type of research is qualitative research. This research uses the literature review method. The results of the study usingÂ the literature study data analysis method, obtained the result that fair value is not always stable and can be fully trusted, especially when the market is illiquid or under pressure.Â So, reasonable value can affect a company's market value, but it doesn't necessarily directly affect its intrinsic value or actual value. This is because fair value is based on the market's valuation of an asset or company at a given time.